Behavioral and EEG Evidence for Auditory Memory Suppression - Cano, Maya E.; Knight, Robert T. (Frontiers in Human Neuroscience, 2016)
The neural basis of motivated forgetting using the Think/No-Think (TNT) paradigm is receiving increased attention with a particular focus on the mechanisms that enable memory suppression. However, most TNT studies have been limited to the visual domain. To assess whether and to what extent direct memory suppression extends across sensory modalities, we examined behavioral and electroencephalographic (EEG) effects of auditory Think/No-Think in healthy young adults by adapting the TNT paradigm to the auditory modality. Behaviorally, suppression of memory strength was indexed by prolonged response times during the retrieval of subsequently remembered No-Think words. We examined task-related EEG activity of both attempted memory retrieval and inhibition of a previously learned target word during the presentation of its paired associate. Event-related EEG responses revealed two main findings: 1) a centralized Think > No-Think positivity during auditory word presentation (from approximately 0-500ms), and 2) a sustained Think positivity over parietal electrodes beginning at approximately 600ms reflecting the memory retrieval effect which was significantly reduced for No-Think words. In addition, word-locked theta (4-8 Hz) power was initially greater for No-Think compared to Think during auditory word presentation over fronto-central electrodes. This was followed by a posterior theta increase indexing successful memory retrieval in the Think condition. The observed event-related potential pattern and theta power analysis are similar to that reported in visual Think/No-Think studies and support a modality non-specific mechanism for memory inhibition. The EEG data also provide evidence supporting differing roles and time courses of frontal and parietal regions in the flexible control of auditory memory.